AMH independently predicts aneuploidy but not live birth per transfer in IVF PGT-A cycles - Howard J. Li; David B. Seifer; Reshef Tal (BMC, 2023)
Abstract Background While anti-Müllerian hormone (AMH) predicts quantitative IVF outcomes such as oocyte yield, it is not certain whether AMH predicts markers of oocyte quality such as aneuploidy. Methods Retrospective case-control analysis of the SART-CORS database, 2014-2016, to determine whether anti-Müllerian hormone (AMH) predicts aneuploidy and live birth in IVF cycles utilizing preimplantation genetic testing for aneuploidy (PGT-A). Results Of 51,273 cycles utilizing PGT-A for all embryos, 10,878 cycles were included in the final analysis; of these, 2,100 cycles resulted in canceled transfer due to lack of normal embryos and 8,778 cycles resulted in primary FET. AMH levels of cycles with ≥ 1 euploid embryo were greater than those of cycles with no normal embryos, stratifying by number of embryos biopsied (1-2, 3-4, 5-6, and ≥ 7), P < 0.017 for each stratum. Adjusting for age and number of embryos biopsied, AMH was a significant independent predictor of ≥ 1 euploid embryo for all age groups: < 35 yrs (aOR 1.074; 95%CI 1.005-1.163), 35-37 years (aOR 1.085; 95%CI 1.018-1.165) and ≥ 38 years (aOR 1.055; 95%CI 1.020-1.093). In comparative model analysis, AMH was superior to age as a predictor of  ≥ 1 euploid embryo for age groups < 35 years and 35-37 years, but not  ≥ 38 years. Across all cycles, age (aOR 0.945, 95% CI 0.935-0.956) and number of embryos (aOR 1.144, 95%CI 1.127-1.162) were associated with live birth per transfer, but AMH was not (aOR 0.995, 95%CI 0.983-1.008). In the subset of cycles resulting in ≥ 1 euploid embryo for transfer, neither age nor AMH were associated with live birth. Conclusions Adjusting for age and number of embryos biopsied, AMH independently predicted likelihood of obtaining ≥ 1 euploid embryo for transfer in IVF PGT-A cycles. However, neither age nor AMH were predictive of live birth once a euploid embryo was identified by PGT-A for transfer. This analysis suggests a predictive role of AMH for oocyte quality (aneuploidy risk), but not live birth per transfer once a euploid embryo is identified following PGT-A.